Time-out! How psychological momentum builds up and breaks down in table tennis - Den Hartigh, R. J. R.; Gernigon, C. (Journal of Sports Sciences, 2018)
The current study examined the development of psychological momentum (PM) in table tennis and the effect of a time-out. Eighty table tennis players were exposed to an audiovisual scenario, in which they either came back from 1-7 to 7-7 in an all-decisive game (positive momentum), or in which the opponent came back from 7-1 to 7-7 (negative momentum). Furthermore, at the score of 7-7 a time-out was called. One group of participants received no specific instructions during the time-out, whereas the other group received task (mastery-approach - MAp) instructions. Overall, PM perceptions increased for participants in the positive momentum condition, but decreased rapidly for participants in the negative momentum condition. In addition, the time-out led to a loss of PM in the positive momentum condition, but to a recovery of PM in the negative momentum condition. The instructions during the time-out did not make a significant difference. Together, these results suggest that scoring patterns in a table tennis game significantly affect the PM of players. Furthermore, a player or coach could benefit from calling a time-out in a negative momentum situation, as this provides an opportunity to psychologically recover